Pengaruh Administrasi Pendidikan dan Supervisi Akademik Terhadap Kinerja Guru pada MAN 1 Bintan Kepulauan Riau - Saripuddin Saripuddin; Lias Hasibuan; Kasful Anwar Us (AkMen JURNAL ILMIAH, 2021)
This study aims to determine and analyze: the effect of educational administration and academic supervision on teacher performance at MAN 1 BintanRiau Islands. This research approach uses survey research. The time of the research was carried out starting in March 2021. The research population was 30 lecturers who taught at MAN 1 Bintan Kijang, Riau Islands. The sample selection in this study was carried out using the census method where the population acted as a sample. The results showed that: 1) There was no positive and significant effect of education administration individually (partial) on teacher performance at MAN 1 BintanRiau Archipelago, with tcount = 0.258 < ttable = 1.99. 2) There is a positive and significant effect of individual (partial) academic supervision on teacher performance at MAN 1 BintanRiau Islands, with tcount = 2.397 > ttable = 1.99. 3) There is a simultaneous (simultaneous) effect of education administration and academic supervision on teacher performance at MAN 1 BintanRiau Islands, where Fcount = 15,467 > Ftable = 2.73. Based on the results of the study, the coefficient of determination (R2 ) was 0.534 or (53.4%). This